JAK2‐V617F‐mediated signalling is dependent on lipid rafts and statins inhibit JAK2‐V617F‐dependent cell growth. (15th November 2012) - Griner, Lori N.; McGraw, Kathy L.; Johnson, Joseph O.; List, Alan F.; Reuther, Gary W.
Summary Aberrant JAK2 signalling plays an important role in the aetiology of myeloproliferative neoplasms (MPNs). JAK2 inhibitors, however, do not readily eliminate neoplastic MPN cells and thus do not induce patient remission. Further understanding JAK2 signalling in MPNs may uncover novel avenues for therapeutic intervention. Recent work has suggested a potential role for cellular cholesterol in the activation of JAK2 by the erythropoietin receptor and in the development of an MPN‐like disorder in mice. Our study demonstrates for the first time that the MPN‐associated JAK2‐V617F kinase localizes to lipid rafts and that JAK2‐V617F‐dependent signalling is inhibited by lipid raft disrupting agents, which target membrane cholesterol, a critical component of rafts. We also show for the first time that statins, 3‐hydroxy‐3‐methyl‐glutaryl coenzyme A (HMG‐CoA) reductase inhibitors, widely used to treat hypercholesterolaemia, induce apoptosis and inhibit JAK2‐V617F‐dependent cell growth. These cells are more sensitive to statin treatment than non‐JAK2‐V617F‐dependent cells. Importantly, statin treatment inhibited erythropoietin‐independent erythroid colony formation of primary cells from MPN patients, but had no effect on erythroid colony formation from healthy individuals. Our study is the first to demonstrate that JAK2‐V617F signalling is dependent on lipid rafts and that statins may be effective in a potential therapeutic approach for MPNs.